2017
DOI: 10.15282/jmes.11.4.2017.7.0273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the use of cutting temperature and tool wear in the turning of mild steel bars

Abstract: The paper is concerned with the development of a data acquisition system for the measurement of temperature used for metal cutting. In this study, machining tests were performed and an analysis of the temperature and wear of the cutting tool is presented herein. In metal cutting operations, the wear of tools is generated largely due to the heat emitted from the cutting zone. Therefore, a coolant is often used to cool down the cutting area and protect the cutting tools. However, because of environmental concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It was found that tool life can be estimated and the production cost can be reduced by using image recognition software and artificial neural network (ANN). The Taguchi Method was also employed to select cutting parameters (tool nose radius, cutting speed, feed rate, and cutting depth) An experimental study [4] in turning mild-steel round bar by using various combinations of federate, cutting depth, and speed was also developed. Through the scanning electron microscope (SEM), the tool wear can be measured.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that tool life can be estimated and the production cost can be reduced by using image recognition software and artificial neural network (ANN). The Taguchi Method was also employed to select cutting parameters (tool nose radius, cutting speed, feed rate, and cutting depth) An experimental study [4] in turning mild-steel round bar by using various combinations of federate, cutting depth, and speed was also developed. Through the scanning electron microscope (SEM), the tool wear can be measured.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) established a mathematical model between cutting parameters and cutting force through multiple regression analysis. Abou-El-Hossein and Kops (2017) explored the influences of cutting parameters on cutting temperature, showing that excessive depth of cut and cutting speed led to high cutting temperatures, which adversely affected tool life. Ţîțu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hossein and Kops's research showed that the cutting temperature increases under larger cutting depth and higher cutting speed, which in turn shortens the tool life. However, the research took time to carry out the cutting work and belonged solely to the research of a single quality and not a multi-quality research [5]. The research of Schultheiss et al which pointed out that reducing the tool wear can shorten the time of the production cycle and reduce energy consumption, was also a single quality research and not a multi-quality research [6].…”
Section: Introductionmentioning
confidence: 99%